2016
DOI: 10.1002/lsm.22549
|View full text |Cite
|
Sign up to set email alerts
|

Near‐IR transillumination and reflectance imaging at 1,300 nm and 1,500–1,700 nm for in vivo caries detection

Abstract: Introduction Several studies suggest that near-IR imaging methods at wavelengths longer than 1,300nm have great potential for caries detection. In this study, the diagnostic performance of both near-IR transillumination and near-IR reflectance was assessed on teeth scheduled for extraction due to orthodontic treatment (n = 109 teeth on 40 test subjects). Methods Three intra-oral near-IR imaging probes were fabricated for the acquisition of in vivo images using a high definition InGaAs camera and near-IR broa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
59
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 36 publications
1
59
1
1
Order By: Relevance
“…Several studies have indicated that light scattering of a tooth enamel surface notably decreases from the visible spectrum to the near‐infrared (NIR), and that wavelengths of 1300−1700 nm have great potential for detecting caries and other diseases . Studies have shown that the NIR illumination (NIRi) method can produce contrast that is sufficient for interproximal/occlusal carious lesion imaging . However, there are several major limitations of the NIRi method.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that light scattering of a tooth enamel surface notably decreases from the visible spectrum to the near‐infrared (NIR), and that wavelengths of 1300−1700 nm have great potential for detecting caries and other diseases . Studies have shown that the NIR illumination (NIRi) method can produce contrast that is sufficient for interproximal/occlusal carious lesion imaging . However, there are several major limitations of the NIRi method.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that in addition to being able to acquire high contrast images of occlusal demineralization with extremely high contrast [1, 2], interproximal lesions well below the surface can be imaged in vivo [3]. Therefore, NIR imaging can be potentially used to guide lasers for the removal of lesions on tooth proximal surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…At 1310 nm, mild fluorosis and other shallow defects may be discernable depending on their severity, geometry, and method of imaging [22]; Hirasuna et al suggest multimodal NIR imaging as a potential means for differentiating between mild fluorosis and deeper caries. Taken altogether, NIR dental imaging has produced condition-dependent applications that challenge or exceed two-dimensional radiographs without the use of ionizing radiation, and work has been done to compare the diagnostic capabilities of both technologies [15], [19], [23].
FIGURE 1.Common NIR imaging modes.
…”
Section: Introductionmentioning
confidence: 99%